Empirical Analysis of the Conceptual Differences and Practical Risks of Denaturalization, Inadmissibility, and Manifest Inadmissibility in Constitutional Actions in Ecuador - Pazmiño Carrera, Cristina (USFQ Law Review, 2025)
One of the most concerning phenomena in Ecuadorian constitutional justice is the abusive use of constitutional actions. On multiple occasions, these mechanisms have been denaturalized for purposes other than the protection of rights, causing serious harm to the administration of justice and to the public treasury. Despite their relevance, the concepts of denaturalization, inadmissibility, and manifest inadmissibility have not been clearly defined either by legal doctrine or by the jurisprudence of the Constitutional Court of Ecuador. This article constitutes the first systematic study to address this issue through a mixed empirical analysis—both qualitative and quantitative—of more than sixty rulings issued by the Court under two different compositions: 2019-2022 and 2022-2025. The findings show how the Court has applied these categories, their conceptual differences, and the practical effects they generate for petitioners, lawyers, and judges. The study concludes that a uniform definition of these figures is essential to reduce judicial discretion, prevent their arbitrary application, and strengthen the right to legal certainty.